Teaching of Arabic in Malaysia - Haji Ibrahim, Majdi; Abd. Rahman, Akmal Khuzairy (IIUM Press, International Islamic University Malaysia, 2018)
The study aims through a deductively descriptive method to focus on the influence of Arabic on the Malaysian culture. The most important milestones of Arabic in the Malaysian context and the most stand out Malaysia public and private institutions which made the most contributions in spreading Arabic in the Malay culture. They study begins with the arrival of Islam and Arabic in the Archipelago as a precursor to uncover the depth of the influence of Arabic in the minds and culture of the Malays. The influence of Arabic on the following aspects will also be discussed: the writing script of the Malay, the educational system in schools and universities, the mass media in addition to the public Malaysian institutions such as the mosques, the public and private companies.